Electrical Conductivity Control System in Pakcoy Plant based on Fuzzy Logic Control - Ma’shumah, Siti; Pramartaningthyas, Ellys Kumala (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
Along with increasing consumption of vegetables as a fulfillment of nutrition in the community, it provides a breakthrough to create a new method of growing vegetables, namely using a system of growing vegetables using water called the hydroponic system. In the hydroponic system here using the Nutrient Film Technique (NFT), the NFT technique is a hydroponic cultivation method where roots grow in a shallow nutrient layer and are circulated so that they will get nutrients, water, and oxygen continuously. One of the important things that is a measure of the success of a hydroponic system is the provision of nutrients to plants correctly. The concentration of nutrient solution that plants need requires a number of different electrical conductivity. In this study to control the pakcoy plant by using fuzzy logic. Which consists of 2 inputs, TDS sensor and ultrasonic sensor. While the output given by the control of this system is the length of the pump opening. The pump for output is divided into 3, the first is the pump for water, the second is the pump for nutrition A and the last is the pump for nutrition B. In this system, hydroponic nutrient control in pakcoy plants has been tried using fuzzy logic control with a success rate of ±70%. This shows that the experiment that has been carried out by the system can run well, namely being able to maintain hydroponic nutrients in pakcoy plants